Consumer-driven technologies in healthcare breakthroughs in research and practice (Critical explorations., 2019)
"This book is a critical source of academic knowledge on the use of smartphones and other technological devices for cancer therapy, fitness and wellness, chronic disease monitoring, and other areas. The tracking of these items using technology has allowed consumers to take control of their own healthcare"--Provided by publisher